PENGGUNAAN ONLINE INTERACTIVE MULTIMEDIADENGAN PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN BERFIKIR KRITIS MAHASISWA CALON GURU PGSD - Imelda Free Unita Manurung; Nurhairani Nurhairani (Universitas Negeri Medan, 2019)
Abstract: Use of Interactive Multimedia Online with the Implementation of Problem Based Learning Models to Improve Critical Thinking Skills of Prospective Teachers in PGSD Teachers. Using of Online Interactive Multimedia with the implementation problem based learning model to increase critical thingking skill for students in PGSD major. This study aims to increase the critical thingking skills of students in PGSD major in state university of Medan. The method used in this study used is a quasi-experimental design with nonequivalent control groupp design. From the results of the t test calculations of two independet samples using SPSS 16 obtained a significance of 0,004. So, it can be concluded that the use of Online Interactive Multimedia with the implementation problem based learning model can increase critical thingking skill for students in PGSD major than the the implementation problem based learning model not using Online Interactive Multimedia.Keywords: Online Interactive Multimedia, Problem Based Learning, Critical Thinking SkillAbstrak: Penggunaan Online Interactive Multimedia Dengan Penerapan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Keterampilan Berfikir Kritis Mahasiswa Calon Guru PGSD. Penelitian ini memiliki tujuan untuk meningkatan keterampilan berfikir kritis mahasiswa calon guru PGSD di Universitas Negeri Medan. Metode yang digunakan dalam penelitian ini adalah kuasi eksperimen dengan desain nonequivalent control group design. Dari hasil perhitungan uji t dua sampel independen dengan menggunakan SPSS 16 diperoleh signifikansi sebesar 0,004 sehingga dapat disimpulkan bahwa penggunaan online interactive multimedia dengan penerapan model pembelajaran problem based learning dapat lebih meningkatkan keterampilan berfikir kritis mahasiswa dibandingkan dengan penerapan model pembelajaran problem based learning tanpa menggunakan online interactive multimedia.Kata Kunci : Online Interactive Multimedia, Problem Based Learning, Keterampilan Berfikir Kritis.